A Bibliometric Study of the Term Workplace Flexibility (West Science Business and Management, 2025)
This study presents a bibliometric analysis of academic literature related to the term “workplace flexibility” to uncover publication trends, thematic structures, and influential contributions within the field. Using data extracted from the Scopus database and analyzed through VOSviewer, the study maps co-authorship networks, international collaborations, keyword co-occurrence patterns, and temporal trends. The findings reveal a concentration of scholarly activity in Western countries, particularly the United States, United Kingdom, and Australia, with significant collaboration among prominent authors such as Kossek E.E., Moen P., and Allen T.D. Keyword analysis identifies four major thematic clusters: employee well-being and satisfaction, labor equity and access, structural scheduling models, and digital/remote work. Temporal overlay mapping indicates a growing research focus on telecommuting, well-being, and productivity in the post-2018 period, reflecting the influence of global workplace transformations. While the field has matured over time, it remains fragmented in terminology and geographically skewed. The study highlights the need for broader global representation, clearer conceptual frameworks, and expanded inquiry into technological and organizational dimensions of workplace flexibility.